The Place of Law in Modern Naturalistic Sociology - Trimailovas, Vladimiras (Problemos, 1982)
The idea grounded in the article is that modern naturalistic sociology being metaphysically orientated was not able to raise correctly the problem of social law. One of the basic categories of naturalism, the so-called “natural law of nature” is discussed. It is concluded that the above category is absolutely inadequate to reflect the nature of the social law.